Efficacy and safety of first-line PD-1/PD-L1 inhibitors combined with or without anti-angiogenesis therapy for extensive-stage small-cell lung cancer: a network meta-analysis - Linjing Zhou; Yuwei Li; Le Wang; Kaiyan Chen; Shichao Zhou; Yunfei Chen; Jing Sun; Yunfeng Tong; Yun Fan (Therapeutic Advances in Medical Oncology)
Background: Immune checkpoint inhibitors (ICIs) combined with chemotherapy, with or without angiogenesis inhibitors, have been investigated as the first-line treatment for extensive-stage small-cell lung cancer (ES-SCLC). However, it remains unclear which treatment modalities are the most effective and safest, as comparative studies evaluating these treatment options are limited. Objectives: This article aims to compare the relative efficacy and safety of ICIs + Chemo + angiogenesis inhibitors versus ICIs + Chemo as the first-line treatment for ES-SCLC. Design: A network meta-analysis was conducted to systematically compare the efficacy and safety data obtained from various clinical trials. Data source and methods: This study presents a systematic review and Bayesian network meta-analysis of data sourced from PubMed, Cochrane Library, EMBASE, ClinicalTrials.gov, and major international conferences up to August 31, 2024. Furthermore, this study analyzed both published works and gray literature on randomized clinical trials (RCTs). Results: A comprehensive analysis was conducted on 10 phase III RCTs comprising 2672 untreated ES-SCLC patients treated with two PD-L1 inhibitor combinations with angiogenesis inhibitors (ICIs + Chemo + angiogenesis) and eight PD-1/PD-L1 inhibitor combinations (ICIs + Chemo). Patients treated with ICIs + Chemo + angiogenesis inhibitors had higher progression-free survival (PFS) (hazard ratio (HR) = 0.56, 95% CI: 0.47–0.66) and overall response rate (ORR) (OR = 1.64, 95% CI: 1.17–2.31) compare to those who were treated with ICIs + Chemo. However, no significant difference was observed in the overall survival (OS; HR = 0.97, 95% CI: 0.79–1.19) and Grade ⩾ 3 adverse events (OR = 1.28, 95% CI: 0.81–2.04) between these patients. The subgroup analyses revealed that the addition of angiogenesis inhibitors improved the OS in patients under 65 years. Moreover, PFS was improved in all subgroups except the central nervous system metastasis. Conclusion: This study revealed that first-line immunochemotherapy combined with angiogenesis inhibitors improves PFS and ORR in ES-SCLC patients; however, it did not affect OS. Therefore, it was inferred that patients under the age of 65 can gain survival benefits from the addition of anti-angiogenic therapy. Trial registration: INPLASY (INPLASY2023110061).